IMPROVING THE STUDENTS SPEAKING SKILL USING ROLE PLAY AT X CULINARY 1 CLASS OF SMKN 8 SURABAYA - Seputra, Gebi Darma (English Language Education Study Program, 2022)
This study is about the use of role play to improve students speaking ability in the case of the X Culinary 1 Class of SMKN 8 Surabaya. The purpose of this study is to find out whether the use of Role Play to improve the students speaking ability.The object of this study was the X Culinary 1 Class of SMKN 8 Surabaya. Total of 36 students from the X Culinary 1 Class of SMKN 8 Surabaya were involved in this study. I used questionnaires to collect the necessary data. The data were in the form of questions, from which the data analysis was done. In conducting the research, I observed the students activities in the role play.From the observation, it was found out that with the use of role play students were more encouraged to speak English, they more often spoke in English, were able to give feedback to other speakers, and used their vocabulary more in order to make their speaking alive.The result of the analysis showed that students spoke more bravely and fluently than before while using role play. I suggested some ways to teach speaking using role play; the teacher should recognize the students experience to make a more simple activity because if they have ever had such a situation they could do the activity easily. The teacher should guide the students to do role play and how to do it well. The teacher should make the students understand the situation in details to give good performance, and if the treatment has done in a long time, it will get a better result.